Analysis of Residual Strength of Inclined Angle Perforating Casing - LI Mingfei; HUANG Jingfu; JIA Hai; DOU Yihua; LIANG Jingwei; SANG Pengfei (Cejing jishu)
In order to increase the effective penetration depth of perforation and establish efficient oil and gas channels, it is often required that the perforation channels should be parallel to the reservoir direction during perforation construction. However, geological structures such as folds and faults often cause the reservoir to be inclined, which results in the channels intersecting the casing at an angle rather than perpendicularly, that is, the casing is perforated at an inclined angle. Inclined perforation breaks through the limitation in existing perforation technology that requires the perforation direction to be perpendicular to the casing. However, after perforation, the perforation holes alter the casing structure. When the casing is subjected to external forces, stress concentration occurs around the holes, reducing the casing's strength. As a result, perforated casings are more prone to damage compared to regular casings. Since there is relatively limited research on the residual strength of casing perforated at inclined angles. In this paper, a three-dimensional finite element model is established to analyze the residual strength of inclined perforated casing. The analysis results show that when the perforation parameters such as hole diameter, hole density, and phase angle are constant, as the perforation inclination angle increases (from 0 to 30°), the remaining external squeeze strength of the casing gradually decreases, and the reduction in the remaining strength of the perforation casing does not exceed 13.00%. When the inclination angle is set to 30° and the phase angle varies from 30° to 180°, the change in the remaining strength of the perforation casing does not exceed 10.20%. When the phase angle is 90°, the remaining strength of the perforation casing is relatively optimal. When the inclination angle is set to 30° and the hole diameter increases from 10 mm to 18 mm, the reduction in the remaining strength of the perforation casing can reach 17.45%. The study can provide theoretical support for the analysis of the remaining strength of inclined perforation casings and practical application in perforation construction.